IDENTIFIKASI BAKTERI ASAM LAKTAT INDIGENOUS DARI BELIMBING WULUH (Averrhoa bilimbi L.) - Murna Muzaifa (Jurnal Sagu, 2014)
The objective of this study was to identify indigenous lactic acid bacteria from bilimbi. Seven isolates wereselected from bilimbi. Isolates were identified by morphological and biochemical characterictics and theirability to ferment carbohydrates. Three species of lactic acid bacteria from bilimbi were identified, asEnterococcus faecalis, Lactococcus lactis subsp. lactis and Lactobacillus plantarum.Key words: bilimbi, isolate, identification, indigenous, lactic acid bacteria